Enhancing Mathematical Disposition in Geometry Instruction : The Role of E-Comics in Realistic Mathematics Education - Trisna Nugraha; Asep Samsudin (PAEDAGOGIA, 2024)
Success in learning mathematics can be measured through five aspects called the five strands of mathematical proficiency. These five aspects need to be taught fairly, resulting in a change in students' mathematical attitudes where this aspect is still minimally looked at and researched. Therefore, the research aims to analyze changes in students' mathematical dispositions by reviewing the role of e-comics in Realistic Mathematics Education (RME). This context-based mathematics learning approach is assumed to provide meaningful learning for students. This mixed-methods research with a sequential explanatory research design was carried out on 30 elementary school students by combining quantitative data collection and analysis techniques with qualitative data support. The research showed that using e-comics in RME learning significantly improved students' mathematical dispositions with a large effect size (Cohen’s effect size = 0,98). In a qualitative review involving data triangulation, evidence was found that using e-comics in RME learning has a role in facilitating the development of each student indicator, as evidenced in the high students’ enthusiasm or response in learning both in observations, questionnaires, and documentation studies. In this way, it is hoped that this innovation can be researched and developed further on a more diverse scale and content. In addition, this research provides further opportunities for research and teacher training related to developing RME learning designs and e-comics in learning.